2012
DOI: 10.4067/s0718-19572012000200019
|View full text |Cite
|
Sign up to set email alerts
|

Paralarvas y juveniles de Octopus bimaculatus (Cephalopoda: Octopodidae) en el Pacífico sur de México

Abstract: Abstract.-The distribution and abundance of Octopus bimaculatus paralarvae and juveniles in the Pacific South of Mexico (i.e., 14 to 16°N) are described. A total of 15 paralarvae were collected during three plankton surveys in July, September and November 2001. Size of paralarvae ranged from 0.7 to 2.7 mm Dorsal Mantle Length (ML), with the smallest size corresponding to the ML at hatching. Additionally, three juveniles were collected by scuba diving in a coastal area in 2010, two small juveniles (7.4 and 9.6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…As in other regions of the Mexican Pacific (off the western coast of the Baja California Peninsula, in the Gulf of California and the rest of the Eastern Tropical Pacific), in July the paralarvae showed predominantly oceanic distribution (Granados-Amores et al, 2010;Alejo-Plata et al, 2013;Staaf et al, 2013). However, the May-June survey included a larger number of stations over the continental shelf of the Gulf of Tehuantepec, and revealed the importance of including the neritic zone in sampling designs of cephalopod paralarvae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other regions of the Mexican Pacific (off the western coast of the Baja California Peninsula, in the Gulf of California and the rest of the Eastern Tropical Pacific), in July the paralarvae showed predominantly oceanic distribution (Granados-Amores et al, 2010;Alejo-Plata et al, 2013;Staaf et al, 2013). However, the May-June survey included a larger number of stations over the continental shelf of the Gulf of Tehuantepec, and revealed the importance of including the neritic zone in sampling designs of cephalopod paralarvae.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, adults of 45-50 species of squid have been registered (Jereb & Roper, 2010) (Alejo-Plata et al, 2013), suggests that these species probably belong to O. compacta (Berry, 1913), O. borealijaponica (Okada, 1927) or O. horstkottei which are distributed in Mexican Pacific waters between 90°-120°W. Morphological and systematic analyses of the family performed by Bolstad (2008Bolstad ( , 2010 demonstrated that O. banksii is only distributed in the Atlantic Ocean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our knowledge on distribution, ecology and biology of small pelagic squids, their larvae, paralarvae and juvenile phases are very limited, particularly in tropical oceans (Vidal et al 2010; Alejo-Plata et al 2013). Pelagic cephalopods are fast-moving animals and are able to detect the approach of sampling gears either by vision or detection of vibrations (Boyle and Boletzky 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The Enoploteuthidae included at least three species of unidentified Abraliopsis and Abraliopsis felis , while the Pyroteuthidae included two unidentified species of Pterygioteuthis . Alejo-Plata et al (2013) recorded cephalopods paralarvae and juveniles in the Gulf of Tehuantepec, noting that six families representing eight genera and at least 13 species were present in the samples. Enoploteuthidae represented 15.9% of specimens and comprise of three unidentified species of Abraliopsis and unidentifed material.…”
Section: Introductionmentioning
confidence: 99%